Déficit municipal y compleja circulación de la figura de la asociatividad territorial. Lectura comparada para comprender el caso colombiano. (2016)
The article discusses the adoption process and precarious development of the principle of territorial associativity. To do this, it previously studies some European states characterized by the highest recognition of democracy and local autonomy and the dynamic momentum of territorial cooperation or merger or abolition of their territorial entities. It is noted that faced with the economic crisis, the fiscal deficit or the inability to comply with the constitutional and legal principles, in addition to the absence of institutional and economic capacities, various proposals of arise of merging, deletion, partnership or cooperation of local entities.. The possibilities of merging or suppression generally have greater resistance to the historical positioning of democracy and local autonomy.